Features of mechanical behavior of EV battery modules under high deformation rate. (October 2019) - Kalnaus, Sergiy; Wang, Hsin; Watkins, Thomas R.; Simunovic, Srdjan; Sengupta, Abhijit
Abstract: We report on changes in material behavior of electric vehicle (EV) Li-ion battery cell modules when the loading speed increases from quasi-static to high speed (close to 1 m/s). A series of out-of-plane indentation experiments were performed on stacks of pouch cells placed in the specially designed enclosure to represent conditions in battery modules. Over one hundred of large format automotive pouch cells were tested under displacement rates differing by orders of magnitude. The details of internal failure were studied by X-ray tomography (XCT). We observe a shift in the force–displacement response from a parabolic behavior characteristic of particulate materials under compression to the response typical of fully dense materials with yield point. This shift is associated with dynamic effects in active materials which result in deep propagation of damage into the battery module, despite the fact that the internal short circuit is triggered when the displacement of the indenter is one half of that under the slow displacement rate.